Assessing perceived crowding of diving sites in Hong Kong. (November 2015) - Zhang, Li-Ye; Qiu, Jian-Wen; Chung, Shan-Shan
Abstract: This study has explored perceived crowding of an underwater environment. Two dimensions were assessed: the number of divers seen and the proximity of divers to each other. Data were obtained from a survey of 216 divers who undertook diving in Hong Kong during 2013–14. Photographs depicting four levels of crowding (number of divers) and four levels of diver proximity in different combinations were shown to the respondents for assessing acceptability. Between the two variables, the "number of divers" was the most influential factor to divers' perceived crowding. Divers' begin to feel unacceptably crowded if 7∼8 divers are visible to them at one time. Based on this, it is likely that the usage of Hong Kong diving sites has already exceeded its social carrying capacity. Implications for future research and diving tourism management for Hong Kong diving sites are also discussed in the paper. Highlights: Demonstrated the rapid appraisal of the social carrying capacity of a diving site. "Number of divers" was the most influential factor for divers' perceived crowding. Divers begin to feel unacceptably crowded if 7 to 8 divers are visible to them at one time. Hong Kong diving sites may already exceeded its social carrying capacity.